Education On Processing Organic Waste Into Liquid Organic Fertilizer Using The ABCD Approach - Delfita, Rina; Mawarni, Lisa Fitri; Nurhaliza, Tetes; Helmita, Roza; Rosmiati, Rosmiati; Zahraini, Zahraini (Jurnal Masyarakat Religius dan Berwawasan, 2025)
Educating high school students about processing organic waste into liquid organic fertilizer using the ABCD (Asset-Based Community Development) approach aims to increase environmental awareness and practical skills among students. In this program, students are involved in a series of workshops that teach the process of processing organic waste through fermentation, as well as the importance of sustainable waste management. The ABCD method focuses on utilizing the potential and resources available in the community, encouraging students to collaborate on practical projects. This method has several stages, namely discovery, design, define and destiny. The stakeholders involved are the principal, biology teacher and 20 students of SMAN 2 Sungai Tarab, Tanah Datar, West Sumatra. Based on the results of the activities that have been carried out, it was found that with the ABCD approach, students of SMAN 2 Sungai Tarab have succeeded in developing their assets in the form of increasing skills in processing organic waste into liquid organic fertilizer and initiating the creation of POC sustainably. Thus, education on processing organic waste into liquid organic fertilizer with the ABCD approach can improve organic waste processing skills and the younger generation's concern for the environment.